Commit ee6200b4 by Robbert Krebbers

### Tweaks.

parent b778f3eb
Pipeline #4252 passed with stage
in 5 minutes and 4 seconds
 ... ... @@ -1136,11 +1136,8 @@ Proof. by destruct (m1 !! i), (m2 !! i). Qed. Lemma map_zip_with_empty {A B C} (f : A → B → C) : map_zip_with f ∅ ∅ = ∅. Proof. unfold map_zip_with. by rewrite merge_empty by done. Qed. Lemma map_zip_with_empty {A B C} (f : A → B → C) : map_zip_with f ∅ ∅ = ∅. Proof. unfold map_zip_with. by rewrite merge_empty by done. Qed. Lemma map_insert_zip_with {A B C} (f : A → B → C) m1 m2 i x y z : f y z = x → ... ... @@ -1151,11 +1148,10 @@ Proof. Qed. Lemma map_zip_with_fmap {A' A B' B C} (f : A → B → C) (g1 : A' → A) (g2 : B' → B) m1 m2 : (g1 : A' → A) (g2 : B' → B) m1 m2 : map_zip_with f (g1 <\$> m1) (g2 <\$> m2) = map_zip_with (λ x y, f (g1 x) (g2 y)) m1 m2. Proof. apply map_eq; intro i. rewrite ?map_lookup_zip_with. rewrite ?lookup_fmap. apply map_eq; intro i. rewrite !map_lookup_zip_with, !lookup_fmap. by destruct (m1 !! i), (m2 !! i). Qed. ... ... @@ -1163,42 +1159,35 @@ Lemma map_zip_with_fmap_1 {A' A B C} (f : A → B → C) (g : A' → A) m1 m2 : map_zip_with f (g <\$> m1) m2 = map_zip_with (λ x y, f (g x) y) m1 m2. Proof. rewrite <- (map_fmap_id m2) at 1. by rewrite map_zip_with_fmap; simpl. rewrite <- (map_fmap_id m2) at 1. by rewrite map_zip_with_fmap. Qed. Lemma map_zip_with_fmap_2 {A B' B C} (f : A → B → C) (g : B' → B) m1 m2 : Lemma map_zip_with_fmap_2 {A B' B C} (f : A → B → C) (g : B' → B) m1 m2 : map_zip_with f m1 (g <\$> m2) = map_zip_with (λ x y, f x (g y)) m1 m2. Proof. rewrite <- (map_fmap_id m1) at 1. by rewrite map_zip_with_fmap; simpl. rewrite <- (map_fmap_id m1) at 1. by rewrite map_zip_with_fmap. Qed. Lemma map_fmap_zip_with {A B C D} (f : A → B → C) (g : C → D) m1 m2 : g <\$> map_zip_with f m1 m2 = map_zip_with (λ x y, g (f x y)) m1 m2. Proof. apply map_eq; intro i. rewrite lookup_fmap. rewrite ?map_lookup_zip_with. apply map_eq; intro i. rewrite lookup_fmap, !map_lookup_zip_with. by destruct (m1 !! i), (m2 !! i). Qed. Lemma map_zip_with_map_zip {A B C} (f : A → B → C) m1 m2 : map_zip_with f m1 m2 = curry f <\$> map_zip m1 m2. Proof. apply map_eq; intro i. rewrite lookup_fmap; rewrite ?map_lookup_zip_with; rewrite ?lookup_fmap. apply map_eq; intro i. rewrite lookup_fmap, !map_lookup_zip_with. by destruct (m1 !! i), (m2 !! i). Qed. Lemma map_fmap_zip {A' A B' B} (g1 : A' → A) (g2 : B' → B) m1 m2 : map_zip (fmap g1 m1) (fmap g2 m2) = prod_map g1 g2 <\$> map_zip m1 m2. map_zip (fmap g1 m1) (fmap g2 m2) = prod_map g1 g2 <\$> map_zip m1 m2. Proof. rewrite map_zip_with_fmap. rewrite map_zip_with_map_zip. rewrite map_zip_with_fmap, map_zip_with_map_zip. generalize (map_zip m1 m2); intro m. apply map_eq; intro i. by rewrite ?lookup_fmap; destruct (m !! i) as [[x1 x2]|]. by rewrite !lookup_fmap; destruct (m !! i) as [[x1 x2]|]. Qed. (** ** Properties on the [map_relation] relation *) ... ...
Markdown is supported
0% or
You are about to add 0 people to the discussion. Proceed with caution.
Finish editing this message first!
Please register or to comment